(3Gdbhd GdeSJXQa aj SaQ Gdedc GdCTQa (B((3CHi GdfUQ bGjJHGi (B901(3g`(B)s - (3GHf GdLjYGf , CMeO Hf jMji TGcQ Hf YHO GdZfj, TgGH GdOjf CHh GdHbGA,J (B930 (3g` s ((3eMeO Hf EHQGgje GdWjHi GdTGaYi s)
(3ChdgG (B:s
(3hHYOaEfg deG Cdge Gddg GdcQje SjOfG bGjJHGi Edi GdeSjQ Edi GdeeGdc GdTGejI hSQfG ai CKQg hQCjfG ef GdHdGO hGdYHGO eG jJYdb Ydi GdEfSGf VHWg s
(3BNQgG (B:s
(3dg Cf jOje CjGe ehdGfG GdTQja fSCd Bejf Bejf dG C QVi HhGMOI MJi CVja EdjgG Cdai Cda BejfG s
(3HChdgG hbas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B270 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B203s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B329 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JGQjN (B210) s
Keywords: (3GdJGQjNs